Preparation, Characterization and Antimicrobial Properties of Some Vanadium(III) and Manganese(III) Complexes of Schiff Bases - Kumar Rastogi, Rahul; Garg, Poonam; Ahmad, Shamim (Asian Journal of Chemistry, 2010)
Few complexes of V(III) and Mn(III) have been prepared by reacting their metal(III) chlorides with pyridine-2-carboxaldehydehydrazinecarboxamide [PCHC], pyridine-2-carboxaldehydethiosemicarbazone [PCTSC], 2,5-dihydroxyacetophenonehydrazinecarboxamide [DHAPHC], 2,5-dihydroxyacetophenonethiosemicarbazone [DHAPTSC], (Schiff-bases) in ethanol medium. The chelates are coloured solids and electrolytes of the type[ML]+n.X-n and [ML2]+n.X-n . The IR spectra of the ligands and complexes suggest involvement of hydroxy group, carbonyl group, thionyl group and azomethine group in bonding through oxygen, sulfur and nitrogen atoms, respectively. The electronic spectra and magnetic data suggest the octahedral and square-pyramidal stereochemistry for the complexes of vanadium(III) and manganese(III), respectively. The ligands and complexes have been tested for their antimicrobial activity.